UPAYA MENINGKATKAN MOTIVASI DAN KESEGARAN JASMANI MELALUI METODE LATIHAN SIRKUIT DI SMAN 12 PADANG - Deri Putra (JURNAL PENDIDIKAN ROKANIA, 2016)
This study aims to determine the motivation and efforts to increase physical freshness through circuit training methods.This type of research is a classroom action research . This research was done class XI grade of SMAN 12 Padang which consists of 287 students. The number of students becoming the object of the study was 30 students selected by purposive sampling technique. The data collection technique used observation and questionnaires . The data analysis technique used is the percentage.The results showed: that the motivation of students and the physical freshness of the students increase after giving actions with cycle 1 and cycle II through circuit training method , it is characterized by the condition of student motivation before the given action on average in the category of medium and low , after giving an motivation action, the children become at very high and high categories . Meanwhile, the physical freshness of students before the given action is in the category of less and very less , after a giving physical freshness measures the average student is in good category. And efforts to improve students' motivation and physical fitness through circuit training method if done properly in continuing to provide a positive influence for the students in the learning process